2022
DOI: 10.1038/s41590-022-01167-5
|View full text |Cite
|
Sign up to set email alerts
|

Dntt expression reveals developmental hierarchy and lineage specification of hematopoietic progenitors

Abstract: Intrinsic and extrinsic cues determine developmental trajectories of hematopoietic stem cells (HSCs) towards erythroid, myeloid and lymphoid lineages. Using two newly generated transgenic mice that report and trace the expression of terminal deoxynucleotidyl transferase (TdT), transient induction of TdT was detected on a newly identified multipotent progenitor (MPP) subset that lacked self-renewal capacity but maintained multilineage differentiation potential. TdT induction on MPPs reflected a transcriptionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…Double fluorescent Cre reporter mice harboring mTOM/mEGFP transgene are widely used to determine the efficacy of Cre-mediated recombination within floxed genes and lineage tracing studies ( Chandran et al, 2021 ; Forte et al, 2022 ; Klein et al, 2022 ). Thus, we utilized mTOM/mEGFP transgene to assess Cre recombination using green fluorescence and immunohistochemical localization of mEGFP, as end-points for protein expression, and the ratio of mEGFP to mTOM transgene expression, as an end-point for gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Double fluorescent Cre reporter mice harboring mTOM/mEGFP transgene are widely used to determine the efficacy of Cre-mediated recombination within floxed genes and lineage tracing studies ( Chandran et al, 2021 ; Forte et al, 2022 ; Klein et al, 2022 ). Thus, we utilized mTOM/mEGFP transgene to assess Cre recombination using green fluorescence and immunohistochemical localization of mEGFP, as end-points for protein expression, and the ratio of mEGFP to mTOM transgene expression, as an end-point for gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…TdT, terminal deoxynucleotidyl transferase, is functionally intrinsic to VDJ recombination during lymphoid development and has been identified as the characteristic lymphoid gene in previous studies 1,11,23 . Furthermore, a recent study in mice demonstrated high TdT expression in lymphoid-biased MPP4s and CLPs but no expression in GMPs 39 . In contrast, the expression level of TdT in the conventional human GMP compartment was clearly bimodal (Figure 3D) and TdT+ subset had expression level as high as CLPs (Figure S3C).…”
Section: Lymphoid Proteomic Features Identified Within the Convention...mentioning
confidence: 95%
“…However, immunophenotyping has limited resolution, and HSPC populations defined by flow cytometry are known to be functionally heterogeneous. This is particularly evident within common myeloid progenitors (CMP) (Paul et al, 2015; Perié et al, 2015) and lymphoid-primed multipotent progenitors (LMPP) (Klein et al, 2022; Nestorowa et al, 2016) as revealed by scRNA-Seq and transplantation experiments. Further high-throughput scRNA-Seq studies charted putative gradual molecular transitions from HSCs toward 8 distinct lineages (Dahlin et al, 2018) including specific stages of erythroid differentiation (Tusi et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…However, immunophenotyping has limited resolution, and HSPC populations defined by flow cytometry are known to be functionally heterogeneous. This is particularly evident within common myeloid progenitors (CMP) (Paul et al, 2015;Perié et al, 2015) and lymphoid-primed multipotent progenitors (LMPP) (Klein et al, 2022;Nestorowa et al, . CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%